A functional haplotype of NFKB1 influence susceptibility to oral cancer: a population‐based and in vitro study. (10th April 2018) - Chen, Fa; Liu, Fengqiong; Yan, Lingjun; Lin, Lisong; Qiu, Yu; Wang, Jing; Wu, Junfeng; Bao, Xiaodan; Hu, Zhijian; Cai, Lin; He, Baochang
Abstract: Genetic variations of NF‐κB and its inhibitor IκB genes and their biological mechanism in oral cancer were not well recognized. The purpose of this study was to evaluate the associations of polymorphisms in NFKB1 and NFKBIA with oral cancer susceptibility, and further explore their potential mechanism in vitro. First, the polymorphisms of NFKB1 and NFKBIA were genotyped through iPLEX Sequenom MassARRAY platform in a case–control study with 425 oral cancer patients and 485 healthy controls. Then, the function was explored by a luciferase reporter assay and an electrophoretic mobility shift assay (EMSA) in human tongue squamous cell carcinoma cell lines. The results indicated that NFKB1 rs28362491 Del/Del and rs72696119 G/G genotypes were associated with the risk of oral cancer, with a strong linkage disequilibrium ( D ′ = 0.991, r 2 = 0.971). Moreover, DG haplotype of NFKB1 also showed a significant increased risk (OR = 1.25, 95% CI: 1.02–1.53, P = 0.030). Dual‐luciferase reporter assays further revealed that the plasmids with DG or IG or DC haplotype transfected with Tca‐8113 cells or CAL‐27 cells had a lower luciferase expression than that with IC haplotype. EMSA demonstrated that 4‐bp ATTG deletion in the promoter of NFKB1 abolished the binding site of transcription factor. Our preliminary findings suggest that the haplotype of rs28362491 and rs72696119 in NFKB1 could act as a novel genetic marker to predict oral cancer risk in the southeast of China, but much more extensive researches still need to be conducted. Abstract : In this work, the function of NFKB1 haplotype (rs28362491 Ins/Del and rs72696119 C/G) were explored by dual‐luciferase reporter assays in human tongue squamous cell carcinoma cell lines. The results revealed that the plasmids with DG or IG or DC haplotype transfected with Tca‐8113 cells or CAL‐27 cells had a lower luciferase expression than that with IC haplotype.